The effects of trip purpose on preferred walking environment and route choice of pedestrians - 422813 Shima Hamidi; Chau, Loon Wai, supervisor; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Perekabentuk Bandar)) - Universiti Teknologi Malaysia, 2009